THE DEVELOPMENT OF TUNALARAS CHILDREN REFERRED FROM PATTREN OF AS PARENT - Mavianti Mavianti (KUMPULAN JURNAL DOSEN UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA, 2018)
The child's early character is formed through the family. Family is the first and main education environment for children. Education in the family is very important and is the main pillar of development of a child's character.